Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Moçambique - recessão antes do boom: Reflexões sobre picos de investimento e novas fontes de gás - Roe, Alan (2018)
Este artigo surge na sequência de um artigo anterior onde se considerou em termos gerais muitas das questões que Moçambique enfrenta hoje em dia na gestão dos seus novos recursos extractivos. Em primeiro lugar descreve-se o pico de investimento já desencadeado pelas novas descobertas de gás em Moçambique. Depois apresenta-se em resumo alguma da literatura mais recente sobre os efeitos desses picos noutros países e contextos. De seguida analisam-se os principais aspectos dos resultados económicos decepcionantes testemunhados até 2018, e analisase selectivamente algumas das implicações destes resultados nas políticas futuras. O artigo conclui explorando a epidemiologia de um grande pico do investimento público — uma questão que tem relevância para o pico adicional que ainda é esperado. Ao seguir esta sequência de argumento, procura-se igualmente compreender melhor diversas questões fundamentais de política geral que surgem no contexto das grandes descobertas de novos recursos.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Extractives and economic diversification in Mozambique: will local content do the trick? (Research Brief 2/2018, 2018)
Research Findings - It is unlikely that the extractives sector can any time soon be used to finance visionary transformation strategies aimed at achieving economic diversification. Due to the country’s fiscal situation and delays in developing the offshore natural gas sector, it seems that extractives will not provide additional revenues for at least another decade, if not longer. If the fiscal crisis results in the further deterioration of the provision of public goods and services, the business environment will become worse for the country’s micro, small and medium-sized enterprises. There is the risk that the gap will widen even further between the skills and entrepreneurial capabilities available in the country, and those required by foreign investment projects and their supply chains. Such a prospect does not match well with the expectations that local content policies can provide the silver bullet for diversifying the economy.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector / setor privado

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Gás para desenvolvimento ou apenas dinheiro? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
O gás de Moçambique pode ser usado para promover industrialização e desenvolvimento rural desde que, a partir de agora, sejam feitas as opções correctas. As actuais prioridades vão para os megaprojectos baseados na exportação, que prometem altos rendimentos mas que, tal como os megaprojectos anteriores, fazem pouco pela criação de empregos ou pela redução da pobreza. Os megaprojectos custando dezenas de bilhões de dólares são essenciais, mas o Conselho de Ministros pode orientar as negociações de maneira a darem a prioridade mais alta à utilização do gás para criar uma indústria nacional e empregos, mesmo que reduza as receitas a curto prazo
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural